Rancang Bangunan Prototype Sitem Monitoring Penurunan Fungsi Kcepatan Motor Listrik I Phase dengan IoT - Belva Pradana Putra Hartono; Sri Mulyanto Herlambang; Jaka Septian Kustanto; Henna Nurdiansari; Akhmad Kasan Gupron (Lembaga Pengembangan Kinerja Dosen, 2026)
Electric motors are vital components in ship operations, particularly within sewage pump systems. However, continuous workloads often trigger temperature increases that lead to a decline in motor performance. This study aims to monitor motor temperature in real-time and analyze its effect on rotational speed (RPM) efficiency. In previous research, data on speed parameters and motor operating conditions were obtained, displayed, and analyzed visually and structurally using LabVIEW. The results showed that this system was effective in monitoring motor operating conditions to prevent performance disruptions. However, the developed monitoring system was still offline and did not support real-time remote monitoring . Future research was recommended to integrate this system with an IoT-based network to support remote surveillance.The research methodology was conducted through a 30-minute dynamic test using an ESP32 microcontroller-based thermocouple sensor and a Node-RED dashboard as the monitoring unit. The obtained data were analyzed using the Simple Linear Regression statistical method. The test results demonstrated a gradual temperature rise from 35°C to 63°C at the 30th minute, which remains within the safe category but requires special attention. This equation exhibits a significant negative correlation, where every 1°C increase in temperature results in performance degradation, specifically a decrease in motor speed by -2.71 RPM. This decline is caused by the increased electrical resistivity in the windings and changes in lubricant viscosity due to overheating. This system is proven effective as a preventive maintenance tool to prevent winding insulation damage and extend the operational lifespan of motors onboard ships.